Gender and Emotional Representation Matter: Own Illness Beliefs and Their Relationship to Obesity - Henning, Carmen; Schroeder, Stefanie; Steins-Loeber, Sabine; Wolstein, Joerg (Frontiers in Nutrition, 2022)
Backround: Current treatments of obesity often fail to consider gender and psychological aspects, which are essential for weight loss (maintenance). The aim of the study was to analyze subjective illness representations (SIRs) of adults with obesity according to the Common Sense Self-Regulation Model (CSM) by assessing their associations with weight-related variables and gender effects of these relationships. Methods: Data was collected via online self assessment between April, 2017 and March, 2018. SIRs were operationalized by the revised Illness Perception Questionnaire (IPQ R) and illness outcomes were defined as BMI, eating behavior, well being, bodyweight satisfaction, and shape concerns.The sample consisted of 427 adults (M = 42.2 years, SD = 10.9; 82% female) with obesity (BMI: M = 42.3 kg/m2, SD = 9.0). Student t tests and multiple hierarchical regression analyses were conducted with the control variables (age and BMI) and subjective illness representations and gender as predictors of the weight related outcome variables. Results: The explanation of outcome variances was moderate to high (19% 43%) except for restraint eating behavior (10%). Subjective illness representations significantly predicted weight related outcomes, especially timeline and emotional representations. Female gender predicted restraint eating behavior and females had worse weight-related outcomes and less stable and more emotional representations of their obesity. Conclusion: The results of this study indicate that gender and subjective illness representations, especially the emotional representation, play an important role for weight-related outcomes. Therefore the assessment of SIRs may constitute an economic tool to identify specific individual deficits of self regulation.